Distributed Fog-based Resource Allocation Hybrid Approach using Metaheuristic Optimizers for Mobile Networks (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:In recent years, the increasing use of the mobile fog server application has generated excessive amounts of data of different types, such as images, documents, multimedia, and other files. The problem  is difficult to manage and control the volume of data used in fog computing, and fog-server computing has problems with latency, resource allocation, and fitness.Materials and Methods:Meta-heuristic algorithm implementation requirements, Harris hawks efficiency criteria for application, and Hybrid algorithm : the proposed Hybrid algorithm based on the combining algorithms Harris hawks optimization algorithm, and Meta-heuristic PSO algorithm. Results:The proposed system results showed that the total latency of PSO is 223.629  seconds, HHO is 167.722 seconds, and decreased latency with Hybrid as 140.943 seconds. Besides, total response times are 253.019 ms, 215.066 , 170.357 for PSO, HHO, and Hybrid respectively. In addition, Average total packet loss rate is 31.131, 27.287, and 16.853 for PSO, HHO, and Hybrid respectively.Conclusion: The results showed that the proposed resource allocation fog-server computing system enhanced overload and computation on each server by balancing incoming wireless mobile requests among available servers as the total latency of PSO is 223.629  seconds, HHO is 167.722 seconds, and decreased latency with Hybrid as 140.943 seconds